The Impact of Leadership Styles and Leaders’ Competencies on Employees’ Job Satisfaction - Ababneh, Omar Mohammed Ali (2009)
Previous studies have documented the impact of leadership styles on employees’job satisfaction. Also, it has been found that leaders’ emotional intelligence plays a significant role in determining leadership styles and predicting employees’ job satisfaction. However, it is argued in this thesis that for leaders to be competent they need to possess a number of competencies not only emotional intelligence. It is against this backdrop that the present study was carried out. Specifically, this study aimed at investigating whether leadership style and leaders’ competencies influence employees’ job satisfaction. To this end, 233 respondents working in various organizations located in Saudi Arabia and Jordan were selected to participate in the study. Leadership style/behaviour was measured by the 20-item Leadership Style Questionnaire developed by Northouse (2001). This instrument has 10 items to measure task-oriented leadership style and 10 items relational/people-oriented leadership style.Leaders’ competencies were measured by the Eight Universal Management and Leadership Competencies in 18 Skill Sets developed by the Profile Service Centre. This instrument contains three items to measure communication, three items for leadership, two items for adaptability, two items for relationships, two items for task management, two items for production, two items for development of others, and two items to measure personal development. Job satisfaction was measured by using the 5-item questionnaire developed by Brayfield and Rothe(1951). The findings revealed that leadership style and leaders’ competencies were statistically and significantly related to overall job satisfaction. Leaders’competencies were found to be the best predictor of job satisfaction. Moreover, it is found that competencies (in addition to emotional intelligence) like communication skills, solving problems, listening effectively, processing information, motivating successfully, delegating responsibilities, building personal relationships, focusing on working efficiently, taking action, and achieving results have a significant effect on forming leadership styles.The limitations of this study and the recommendations for future research are also discussed.